THE REPRESENTATION OF TABAYYUN AS AN ISLAMIC COMMUNICATION ETHIC IN THE FILM TABAYYUN (2025) - Muh Azhari (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
The rapid proliferation of unverified information in contemporary social life has elevated the urgency of ethical communication practices grounded in Islamic values. This study investigates the representation of tabayyun as an Islamic communication ethic within the Indonesian religious drama film Tabayyun (2025). The concept of tabayyun, rooted in QS. Al-Hujurat [49]: 6, refers to the deliberate verification of information prior to judgment or action. Employing a qualitative methodology with content analysis, this research systematically examines scenes, dialogues, and visual symbols to trace how tabayyun is constructed and communicated through cinematic narrative. Three principal findings emerge: first, the film illustrates how the absence of tabayyun generates prejudice and social stigma; second, it portrays tabayyun as an active communicative process demanding courage and moral accountability; and third, it demonstrates that sustained practice of tabayyun facilitates conflict resolution and relational reconciliation. This study affirms that tabayyun operates not merely as a religious norm but as a transformative mechanism of ethical communication relevant to contemporary social challenges.